Insecure attachment and impaired reflective functioning mediate the association between childhood trauma and grazing behavior - Rossi, Alessandro Alberto; Tagliagambe, Andrea; Mannarini, Stefania; Dalla Ragione, Laura (Frontiers in Psychology, 2025)
IntroductionGrazing represents a clinically significant eating behavior characterized by repetitive consumption of small amounts of food, often associated with poor outcomes in bariatric surgery populations. Despite growing evidence linking childhood traumatic experiences to disordered eating, the specific psychological mechanisms underlying grazing behaviors remain poorly understood. Developmental theories suggest early relational trauma may disrupt attachment patterns and impair emotional self-regulation through mentalization deficits, which could lead to disordered eating behaviors. However, this pathway does not appear to have been tested. This study examined whether attachment insecurity and impaired reflective functioning mediate the relationship between childhood trauma and grazing behaviors.MethodA cross-sectional study was conducted with 681 Italian adults. Participants completed self-report measures. Structural equation modeling with latent variables and bootstrap resampling (5,000 iterations) was used.ResultsThe model demonstrated satisfactory fit and supported the hypothesized pathways. Childhood traumatic experiences were associated with both attachment anxiety and attachment avoidance. However, only attachment anxiety significantly mediated the relationship between childhood trauma and impaired reflective functioning. Impaired reflective functioning emerged as the strongest predictor of grazing behaviors. The complete mediation pathway through attachment anxiety and impaired reflective functioning was statistically significant, with the model explaining 36.4% of variance in grazing behaviors.DiscussionThese findings provide empirical support for a trauma-informed developmental model of grazing behaviors. The results highlight attachment anxiety and impaired reflective functioning as crucial mediators linking early relational trauma to problematic eating patterns. Clinical implications suggest mentalization-based interventions targeting attachment insecurity may be particularly beneficial for individuals with trauma histories presenting with grazing behavior.